2022
DOI: 10.1108/ecam-02-2022-0128
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Contractor’s core competencies in post-COVID-19 scenario: developing a survey instrument

Abstract: PurposeConstruction industry is one of the worst affected sectors due to the impact of the current coronavirus disease 2019 (COVID-19) outbreak. Therefore, the purpose of this study was to identify the key competencies that should be demonstrated by the contractors in the post-COVID-19 scenario to make them resilient to the adverse impact of pandemic outbreaks.Design/methodology/approachA survey instrument was developed using an extensive literature review and was tested using a pilot study. It was then admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Reimagining for the next normal is crucial for the construction industry to recover from the COVID-19 pandemic shock. Managing the site safety, leadership skills, technical competence, and supply chain disruption were highlighted as the core competencies for the contractors in the post-COVID-19 construction industry (Cai et al, 2021;Deep et al, 2022). Additionally, industry leaders and professionals should create detailed business plans by scrutinizing the current post-COVID-19 market situations and trends (Hook, 2020).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reimagining for the next normal is crucial for the construction industry to recover from the COVID-19 pandemic shock. Managing the site safety, leadership skills, technical competence, and supply chain disruption were highlighted as the core competencies for the contractors in the post-COVID-19 construction industry (Cai et al, 2021;Deep et al, 2022). Additionally, industry leaders and professionals should create detailed business plans by scrutinizing the current post-COVID-19 market situations and trends (Hook, 2020).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Managing the site safety, leadership skills, technical competence, and supply chain disruption were highlighted as the core competencies for the contractors in the post-COVID-19 construction industry (Cai et al. , 2021; Deep et al. , 2022).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…In the Netherlands and globally, notwithstanding the war in Ukraine (Harper, 2022), and the ongoing impact of Covid-19 pandemic on supply chains (Alicke et al, 2020;Deep et al, 2022;Sarkar et al, 2022), there are numerous business-related CE hurdles, such as, products being designed for long-term usage (transition from make-to-break economy), the acceptance of second-hand products by consumers, return-logistics of products, amended financial balance sheet structure with reduced investment opportunities for the company and CE friendly business models (Kirchherr et al, 2017). In an organizational context, adopting CE values requires strategic commitment of the management board with a view to the next step of implementing return logistics and CE values (Bernon et al, 2018).…”
Section: Literature: Construction and Ce In Netherlands And Beyondmentioning
confidence: 99%
“…In the Netherlands and globally, notwithstanding the war in Ukraine (Harper, 2022), and the ongoing impact of Covid-19 pandemic on supply chains (Alicke et al. , 2020; Deep et al. , 2022; Sarkar et al.…”
Section: Literature: Construction and Ce In Netherlands And Beyondmentioning
confidence: 99%
“…During the spread of the new coronavirus, government agencies imposed many construction regulations on construction sites, and there were changes in the workflow and wearing of anti-epidemic equipment on construction sites. Some studies have found that the critical competence of the post-COVID-19 construction industry includes managing site safety, leadership skills, technical competence, managing supply chain disruption, and financial stability [5]. Managing site safety is considered to be the most important competency of the post-COVID-19 construction industry.…”
Section: Introduction Environment Of a Construction Sitementioning
confidence: 99%